On-line solid-phase extraction of pharmaceutical compounds from wastewater treatment plant samples using restricted access media in column-switching liquid chromatography-tandem mass spectrometry - Marasco Júnior, César A. [UNESP]; Sartore, Douglas M.; Lamarca, Rafaela S. [UNESP]; da Silva, Bianca F. [UNESP]; Santos-Neto, Álvaro J.; Lima Gomes, Paulo Clairmont F. de [UNESP] (Elsevier, 2021)
An on-line solid phase extraction using a lab-made restricted access media (RAM) was developed as sample preparation procedure for determination of the pharmaceutical compounds caffeine (CAF), carbamazepine (CBZ), norfloxacin (NOR), ciprofloxacin (CIP), fluoxetine (FLX) and venlafaxine in wastewater treatment plant samples by liquid chromatography-tandem mass spectrometry (LC-MS/MS). This method is suitable for use in routine of analysis, avoiding cross-contamination and requiring only a small sample volume (50 µL), with minimal handling. The method was validated according to international guidelines. The chromatographic efficiency was evaluated using peak resolution and asymmetry parameters. Carryover was also evaluated, in order to ensure reliability of the analysis and the ability to reuse the cartridge. Satisfactory linearity (r2 > 0.99) was obtained for all the compounds. The intra- and inter-day precision values were lower than 5.79 and 14.1%, respectively. The limits of detection ranged from 0.01 to 3 µg L−1 and the limits of quantification were from 0.1 to 5 µg L−1. The method was applied to 20 environmental wastewater samples, with caffeine being the most widely detected compound, at the highest concentration of 392 µg L−1, while other compounds were detected in fewer samples at lower concentrations (up to 9.60 µg L−1). The lab-made modification is a cheaper option for on-line sample preparation, compared to commercially available on-line SPE cartridges and RAM columns. Moreover, a high-throughput procedure was achieved, with an analysis time of 16 min including sample preparation and chromatographic separation. The same RAM column was applied over 200 injections including method optimization, validation and application in wastewater samples without loss of analytical response.
Keywords: Emerging contaminants; Liquid chromatography; Mass spectrometry; Restricted access media; Wastewater